Análise da atividade de trabalho profissional de gerentes de hotel à luz da abordagem da ergonomia - Leite, Cyntia Maria de Gois (2013)
This Masters degree dissertation presents a research that aims at analyzing the activities regarding within a hotel managers work in Natal/RN - Brazil, This Masters degree dissertation presents the research that aims at analyzing the activities regarding the hotel managers work in Natal / RN - Brazil, performing diagnosis of their activities and relating the aspects that impact the quality and productivity of hotel services and managers occupational health. This research is characterized as a case study with a qualitative approach, taking the method of Ergonomic Work Analysis which is the analysis of the managers work activity as a reference to the focus; and combining the use of observational and interactional methods. Ergonomics and macroergonomics are used in this study not only to understand the physical, cognitive and organizational constraints of the manager s duties, but also to characterize the work organizational architecture and design of that hotel. High workload, accumulation of tasks and diversion of functions performed by managers were noticed, increasing thereby the physical and psychological suffering for them. It was found that the activity of managers is characterized by the ambivalence of power, limited autonomy, cooperation, interdependence between managers and the fear of incompetence. It was also noticed that managers devote more time to the day job (37%), another time to sleep (30%), while only 33% of the rest of the day are meant for activities like taking care of health, family, social life and study. Although there are few studies addressing the health and safety of hotel managers, this research revealed that 84% of the surveyed hotel managers complain of musculoskeletal pain which 50% are obese and are 100% sedentary. It was also observed that managers adopt unsuitable postures for carrying out the work activities that contribute to becoming injured or work-related musculoskeletal disorders in the near future. Ergonomic measures were recommended as an investment in the skills and the training of managers, encouraging cooperative work, appropriateness of workload, limiting overtime, preserving the enjoyment of breaks during work and weekly holidays, changing the layout of the work sector , usage of communication technology to prevent displacement, compensatory physical activities, furniture adaptation, among others